APPLICATION OF KINEMASTER-BASED AUDIO VISUAL LEARNING MEDIA IN THE SUBJECT OF SOCIAL SCIENCES AT SMPN 1 KALITIDU - Fitah Rizqia Rahmawati; Sugiyanto Sugiyanto; Chatarina Muryani (GeoEco, 2025)
The learning outcomes of grade VII students during the exam were still relatively low because out of 35 students, 15 students scored above the Minimum Completion Criteria (KKM) of 75 and 20 students scored below the Minimum Completion Criteria of KKM 75. The data proves that students' spatial thinking skills are still weak and can cause difficulties in interpreting maps in social studies geography learning. The ineffective use of computer laboratories and android-based mobile phones in the learning process is one of the causes. The purpose of this study was to analyze the effectiveness of kinemaster-based audiovisual learning media in social studies geography learning at SMP Negeri 1 Kalitidu. The results showed that in the control class the average pre-test score was 43.43 while the average post-test score was 51.25, still lower than the experimental class. In the experimental class the average pre-test score was 45.62 while the average post-test score was 80.93 higher than the control class. The average posttest score for the experimental class > control class was 80.93 > 51.25, which means that the learning outcomes of the experimental class were higher than those of the control class. In the paired t-test, the results obtained were sig.2 tailed at 0.000 < 0.05 Kinemaster-based learning is more effective.